Model Kepemimpinan Transformasi Birokrasi (Studi Penelitian Kabupaten Kebumen Era Kepemimpinan Dra. Hj. Rustriningsih, M.Si.) - Muhammad Hakam Ulfi Ikfina; Dyah Mutiarin (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to know: 1) the regent Rustriningsih transformational leadership style, and 2) the transformation ofthe bureaucracy in Kebumen district under the leadership Rustriningsih from 2000 until 2008. Deskiriptif researchusing qualitative methods with case study approach. Collecting data through interviews and documentation. Interviewswere conducted to Rustriningsih former Regent of Kebumen and the four officials in Kebumen who have theleadership of Rustriningsih namely: the head of the Forest Service, Asekwilda 2, Secretary, and the Chairman ofParliament Kebumen. Data were analyzed through the stages of data reduction, data display and conclusion orverification. The results showed: First, transformational leadership is characterized by the idea or decision Rustriningsihin improving government bureaucracy in the public service. One stop service, e-government, direct mail, Ratih TV, InFM as the radio broadcast area, and positions in the government auction Kebumen prove Rustriningsih prominentleadership. Second, the transformation of the bureaucracy appears from the performance of the bureaucracy indelivering services to the public / community Kebumen. The local government to open a dialogue with many stakeholdersin making policy, looking at society as a customer to be served a maximum, in collaboration with communityorganizations and the private sector in providing services to the public, works by adjusting the will or the needs of thecommunity and the market, and seek transparency.